Birth weight and perfluorooctane sulfonic acid: a random-effects meta-regression analysis - Dzierlenga, Michael W. (Environ Epidemiol, 2020)
Perfluorooctane sulfonic acid (PFOS) is a ubiquitous environmental contaminant. Most people in developed countries have detectable serum concentrations. Lower birth weight has been associated with serum PFOS in studies world-wide, many of which have been published only recently. METHODS: To facilitate a causal assessment of the birth weight and PFOS association, we updated previous meta-analyses of the association and employed a method that facilitated inclusion of all available data in one analysis. Our analysis was based on observations from 29 studies. RESULTS: The random effects summary was −3.22 g/ng/ml (95% confidence interval [CI] = −5.11, −1.33). In a subgroup analysis stratified by when in pregnancy the PFOS concentration was measured, the summary for the early group was −1.35 (95% CI = −2.33, −0.37) and for the later group was −7.17 (95% CI = −10.93, −3.41). In a meta-regression model including a term for timing of blood draw, the intercept was slightly positive but essentially zero (0.59 g/ng/ml, 95% CI = −1.94, 3.11). In other words, the model indicated that when blood was drawn at the very beginning of pregnancy, there was essentially no relation of birth weight to PFOS. The results from the subgroup analyses differed from those from the model because the average gestational age at blood draw in the early group was 14 weeks, when bias would still be expected. A stronger inverse association in Asian studies was not completely explained by their blood draws being from later in pregnancy. CONCLUSIONS: The evidence was weakly or not supportive of a causal association.